Characterisation of a cyclophilin isoform in Trypanosoma cruzi - Bua, Jacqueline (2001)
Fil: Bua, Jacqueline. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología Dr. Mario Fatala Chaben; Argentina.